Caracterização de marcadores moleculares com aplicabilidade para identificação de duas espécies de peixe com interesse forense: Prochilodus argenteus e Prochilodus costatus - Aline Torres de Azevedo Chagas (2015)
The increasing concern about environmental issues added to specific legislation aiming inhibition of environmental damage brought give rise to new challenges for forensic science. Regarding fishing activities, there are several laws with purpose of protecting fishing resources. On the other hand, the correct identification at species-level of samples seized in enforcement actions is far from accurate. Thus, it became extremely important the establishment of techniques that enable the correct identification of the seized samples, ideally through easy handling protocols. This would strength the enforcement actions and the juridical proof. Considering this, molecular techniques can provide species-specific markers for unambiguously identification. This information is important in juridical process for determining if seized samples are indeed one of the ones of prohibited fishing. The aim of this study was to characterize molecular markers for two fish species: Prochilodus argenteus and Prochilodus costatus. Both species present great ecological and economic relevance in São Francisco River Basin. The genomic DNA of both species were sequenced and a de novo assembly was carried out, as well as the annotation of mitochondrial DNA sequences and its comparison to the mitogenomes of a closely related species: Prochilodus lineatus. Genus-specific and species-specific markers were selected considering its potential ability of genus and species identification based just on the PCR products sizes through electrophoresis gel. One pair of genus-specific primers presented highly sensitivity and specificity for Prochilodus genus. Regarding species-specific primers, one pair proved to be specific for P. argenteus. The present study was also able to extract DNA from fishing artefacts used for P. argenteus and P. costatus capture. Prochilodus DNA was detected in those artefacts through PCR using mitochondrial markers. Genomic DNA sequencing also enabled the identification of dozens of thousands microsatellites markers. Later, they are going to be evaluated for species identification and genetic diversity studies. The methodology presented in this project can be potentially applied to other species and used for molecular ecology studies, conservation genetics and in the forensic science, establishing crimes materiality and, consequently, strengthening the juridical proof.